Organisational context of hospitals that participated in a multi-site mentored medication reconciliation quality improvement project (MARQUIS2): a cross-sectional observational study - Jeffrey L Schnipper; Sunil Kripalani; Deonni P Stolldorf; Amanda S Mixon; Mary Dietrich (BMJ Open)
Objectives Medication reconciliation (MedRec) is an important patient safety strategy and is widespread in US hospitals and globally. Nevertheless, high quality MedRec has been difficult to implement. As part of a larger study investigating MedRec interventions, we evaluated and compared organisational contextual factors and team cohesion by hospital characteristics and implementation team members’ profession to better understand the environmental context and its correlates during a multi-site quality improvement (QI) initiative.Design We conducted a cross-sectional observational study using a web survey (contextual factors) and a national hospital database (hospital characteristics).Setting Hospitals participating in the second Multi-Centre Medication Reconciliation Quality Improvement Study (MARQUIS2).Participants Implementation team members of 18 participating MARQUIS2 hospitals.Outcomes Primary outcome: contextual factor ratings (ie, organisational capacity, leadership support, goal alignment, staff involvement, patient safety climate and team cohesion). Secondary outcome: differences in contextual factors by hospital characteristics.Results Fifty-five team members from the 18 participating hospitals completed the survey. Ratings of contextual factors differed significantly by domain (p<0.001), with organisational capacity scoring the lowest (mean=4.0 out of 7.0) and perceived team cohesion and goal alignment scoring the highest (mean~6.0 out of 7.0). No statistically significant differences were observed in contextual factors by hospital characteristics (p>0.05). Respondents in the pharmacy profession gave lower ratings of leadership support than did those in the nursing or other professions group (p=0.01).Conclusions Hospital size, type and location did not drive differences in contextual factors, suggesting that tailoring MedRec QI implementation to hospital characteristics may not be necessary. Strong team cohesion suggests the use of interdisciplinary teams does not detract from cohesion when conducting mentored QI projects. Organisational leaders should particularly focus on supporting pharmacy services and addressing their concerns during MedRec QI initiatives. Future research should correlate contextual factors with implementation success to inform how best to prepare sites to implement complex QI interventions such as MedRec.